Faktor Intensi Berasuransi Syariah: Pengetahuan dan Citra, Kepercayaan Sebagai Variable Mediasi - Amran, Ellyana (Coopetition : Jurnal Ilmiah Manajemen, 2024)
Indonesia as a country with a majority Muslim population, in fact, shows that the penetration of Islamic insurance is still very low compared to conventional insurance. The purpose of this study is to explain the effect of knowledge and product image on Islamic insurance intention in high school teachers in the DKI Jakarta area, mediated by trust. Jakarta, as the center of government and the center of economic activity, has multiple roles and is multi-ethnic and multi-cultural with complex problems. This research uses qualitative and quantitative analysis with a sample size of 270 respondents, taken with the purposive sampling technique. Data were collected and processed using the structural equation model methodology. The results of the analysis show that there is no effect of knowledge on Islamic insurance intentions; product image affects Islamic insurance intentions; both knowledge and product image affect Islamic insurance intentions mediated by trust.